Augmenting nitrogen removal by periphytic biofilm strengthened via upconversion phosphors (UCPs). (February 2019) - Wang, Yu; Zhu, Yan; Sun, Pengfei; Liu, Junzhuo; Zhu, Ningyuan; Tang, Jun; Wong, Po Keung; Fan, Hua; Wu, Yonghong
Graphical abstract: Highlights: UCPs were first used to stimulate nitrogen removal of periphytic biofilms. UCPs optimized the microbial community structure of periphytic biofilms. Periphytic biofilms simulated by UCPs could adapt to nitrogen fluctuation. Abstract: The application of periphytic biofilm in removing nitrogen from water is limited by the fluctuating nitrogen concentration. Here, we delineate a novel approach to enhance periphytic biofilm performance in nitrogen removal via upconversion luminescence of upconversion phosphors (UCPs). Nitrogen removal rates (14 d) in high nitrogen wastewater (26 mg/L) were significantly improved to 58.6% and 61.4% by UCPs doped with Pr 3+ and Li + and UCPs doped with Pr 3+, respectively, and to 95.1% and 95.9% in low nitrogen surface water (2 mg/L), respectively. The stimulation of UCPs optimized the microbial community structure in the periphytic biofilms, and also resulted in good acclimation to use different carbon sources. The enhanced synergic action of cyanobacterial biomass, ratio of Gram +ve to Gram −ve bacteria and carbon source metabolic capacity contributed to the improved nitrogen removal. This novel approach is promising in nitrogen removal from wastewater and surface water with fluctuating initial nitrogen concentration.